Transactive Memory Systems and Acquisition Performance: A Strategic Decision Making Process Perspective - Lou, Bowen; Bauer, Florian; Samba, Codou; Shepherd, Neil (Journal of Management Studies, 2025)
AbstractDuring the pre‐merger phase of an acquisition, fundamental decisions are made concerning whether to buy, which company to buy, and how much to pay. Further, acquisitions carry significant firm‐wide implications requiring input from multiple different specializations, and hence, they are the product of the judgements, decisions, and social interactions between top managers. We focus our theory development on a pivotal yet under‐researched top management team characteristic, transactive memory system (TMS). TMS is the shared division of cognitive labour with respect to encoding, storing, and retrieving knowledge from individual areas of expertise. We theorize that TMT transactive memory directly influences the strategic decision making process, which in turn determines acquisition performance. We test our hypotheses with a sample of 109 acquisitions, combining survey and archival data. We find that TMT transactive memory increases reliance on expert intuition and procedural rationality, while reducing political behaviour; and each of these three strategic decision processes carries different implications for acquisition performance. Our study advances theory by explaining the team‐level behavioural mechanisms that underlie acquisition performance.